2014
DOI: 10.1371/journal.pgen.1004146
|View full text |Cite
|
Sign up to set email alerts
|

Serine Carboxypeptidase SCPEP1 and Cathepsin A Play Complementary Roles in Regulation of Vasoconstriction via Inactivation of Endothelin-1

Abstract: The potent vasoconstrictor peptides, endothelin 1 (ET-1) and angiotensin II control adaptation of blood vessels to fluctuations of blood pressure. Previously we have shown that the circulating level of ET-1 is regulated through its proteolytic cleavage by secreted serine carboxypeptidase, cathepsin A (CathA). However, genetically-modified mouse expressing catalytically inactive CathA S190A mutant retained about 10–15% of the carboxypeptidase activity against ET-1 in its tissues suggesting a presence of paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…Although, the markedly increased endothelin-1-specific immunoreactivity has been demonstrated in CTSA deficient galactosialidosis patient's brain, we did not observe any difference neither in brain nor in liver from CTSA S190A mice using ELISA (Itoh et al, 2000). We also speculate that higher expression of other carboxypeptidases such as Scpep1 may contribute modulating the catabolic proteolysis of Endothelin-I in these tissues (Pshezhetsky and Hinek, 2009; Pan et al, 2014). …”
Section: Discussionmentioning
confidence: 98%
“…Although, the markedly increased endothelin-1-specific immunoreactivity has been demonstrated in CTSA deficient galactosialidosis patient's brain, we did not observe any difference neither in brain nor in liver from CTSA S190A mice using ELISA (Itoh et al, 2000). We also speculate that higher expression of other carboxypeptidases such as Scpep1 may contribute modulating the catabolic proteolysis of Endothelin-I in these tissues (Pshezhetsky and Hinek, 2009; Pan et al, 2014). …”
Section: Discussionmentioning
confidence: 98%
“…These enzymes are lysosomal proteins, which is in line with the important role of NPC1 in lysosomes. SCPEP1 shows homology with CTSA ( Kollmann et al, 2009 ) and a study with double knockout of SCPEP1 and CTSA suggests they share the same peptide substrate ( Pan et al, 2014 ). Single knockout of SCPEP1 in mice resulted in viable mice without lysosomal impairment ( Kollmann et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice containing Ser190Ala point mutation in the CathA active site (CathAS190A strain) and those with the Scpep1 gene interrupted by gene-trap technology (Scpep12/2 strain) were generated as previously described[ 21 , 22 ]. Mice were housed in an enriched environment with continuous access to food and water, under constant temperature and humidity, on a 12 h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies from our laboratory defined a novel pathway for enzymatic inactivation of circulating ET-1 involving two lysosomal/secreted serine carboxypeptidases, cathepsin A (CathA) and serine carboxypeptidase 1 (Scpep1)[ 20 , 21 ]. In particular, we showed that mice with double deficiency of CathA and Scpep1 developed a persisted hypertension and demonstrated a prolonged half-life of circulating ET-1 as well as a more pronounced vasoconstriction in response to low pharmacological doses of this peptide[ 21 ].…”
Section: Introductionmentioning
confidence: 99%